IMPACT OF PATIENT COUNSELING ON HEALTH KNOWLEDGE AND MEDICATION ADHERENCE IN ASTHMA AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE PATIENTS - P, UNNATI; S, ANUSHREYA; KEERTHANA G, GABRIELA; P, MOUNICA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study evaluated the impact of clinical pharmacist-led intervention in health knowledge and medication adherence of Asthma and chronic obstructive pulmonary disease (COPD) patients. Methods: Questionnaires were designed to assess Health knowledge for Asthma and COPD separately. Medication adherence was measured by using the Morisky Medication Adherence Scale-8. Pre-counseling patient responses were recorded. Patient counseling was given regarding the disease condition, medications, and medication use at baseline visit. Patient responses were re-measured upon follow-up visit. The data extracted were tabulated, statistically analyzed and the results were obtained. Results: A total of 141 patients completed the study. Before counseling, the mean (±standard deviation) of knowledge and adherence levels were found to be 8.51±3.36 and 5.01±2.11, respectively. After counseling, they increased up to 12.72±2.16 for knowledge (p<0.0001) and 6.60±1.35 (p<0.0001) for medication adherence. The majority of subjects had about 11–30% increase in knowledge as well as medication adherence. Male patients were more adherent to their medication regime than females. Conclusion: The study demonstrates the positive impact of education and counseling provided by a clinical pharmacist in achieving better therapeutic outcomes – through improvement in medication adherence and health knowledge. In conclusion, continuous education programs and patient counseling should be conducted for chronic diseases to reiterate the importance of medication adherence and, in turn, prevent recurrences, arrest disease progression, minimize hospitalization, and ultimately improve quality of life.